ANÁLISIS DE LAS CONDICIONES OPERATIVAS DEL TANQUE VERTICAL PR-001 DE CAPACIDAD NOMINAL DE 500 BARRILES PARA ALMACENAMIENTO DE DIÉSEL UBICADO EN LA PARROQUIA 7 DE JULIO CANTÓN SHUSHUFINDI - Quilumba Ruiz , María Valeria (2023)
Storage tanks are commonly used in industries to store crude oil and its derivatives, in this case as the PR-001 diesel storage tank. This type of tank requires periodic inspections at different time intervals, in order to be able to analyze the settlement, roundness, and verticality, it is said that abnormalities may occur due to its long-term use.